Politeness in Criticizing Political Discourse: A Model Design - Agustina, Agustina; Nurizzati, Nurizzati; Gani, Erizal; Adek, Muhammad; Elpalina, Srimutia (Humanus, 2023)
The design of this model is based on previous research findings that show the existence of 'verbal violence' in criticizing politicians during political discourse. This violence stems from the type of criticism, the strategy used to criticize, and the dominant style of criticism which is often sarcastic and cynical. As a result, the illocutionary function is conflictive and competitive, which poses a high level of face threat and falls within the impolite category. Based on these findings, a politeness model was developed to criticize political discourse. The model was designed using research and development methods with six stages: needs analysis, model design, model development, model implementation, and model evaluation. Data was collected through media review, and data validation was conducted using expert and user validation. Data analysis was done through content analysis and model development. Given that political discourse is characterized by a struggle for power, the model aims to reduce and soften the illocutionary power of criticism by applying relevant politeness principles and scales. The model is implemented using declarative and interrogative constructions, fenced imperative pragmatic meanings, and soft cues to produce polite criticism while maintaining the competitive atmosphere of political contestation. Therefore, the novelty of this research lies in using linguistic tools to produce a model of polite criticism without reducing the competitive atmosphere that characterizes political contestation. Additionally, the model can contribute to revitalizing political culture by increasing political discourse literacy through linguistic competence. It also presents an alternative solution to the problem of intolerance in the country.